Differences between possession football teams and direct football teams that lead to winning in English Premier League 2016/2017 / Muhammad Ariff Hafizi Abd Rahim - Abd Rahim, Muhammad Ariff Hafizi (2018)
The ultimate purpose of this study was to identify the differences style of attacking patterns between possession football teams and direct football teams that lead to winning in English Premier League 2016/2017. The sample size in this study was 79 videos (N=79) of English Premier League 2016/2017 and it divided into possession football teams and direct football teams. The data will be analyze by using independent T-test to seek the differences between two group (p<0.05). The findings shown there are significant different in term of successful short pass from center area for possession football teams (M=324.97, SO=96.37) and direct football teams (M=168.07, SO=45.60),(p<0.05), unsuccessful short pass right for possession football teams (M=10.02, SO=4.06) and direct football teams (M=7.47, SO=3.70) ),(p<0.05), unsuccessful long pass center for possession football teams (M=17.28, SO=8.01) and direct football teams (M=27.13, SO=8.57),(p<0.05), unsuccessful long pass right for possession football teams (M=5.78, SO=4.33) and direct football teams (M=8.73, SO=4.37), (p<0.05), successful shoot inside penalty box for possession football teams (M=4.19, SO=2.10) and direct football teams (M=3.53, SO=1.36), (p<0.05) and unsuccessful shoot outside penalty box for possession football teams (M=5.58, SO=3.00) and direct football teams (M=3.47, SO=2.13), (p<0.05) between possession football teams and direct football teams in English Premier League 2016/2017. The result show that p value <0.05. Due to this null hypothesis was accepted to reject. The others variable show there is no significant different data and the p value >0.05. The present study revealed that the outcome can be used by team manager, coaches and team analyst to create the best formula for the team and develop systematic training program. Hence, it will improve the athlete performance and will improve the quality of play during the competition.